Benefit-cost analysis financial and economic appraisal using spreadsheets - Campbell, Harry F. 1945- (Cambridge University Press, 2003)
Benefit-Cost Analysis offers the perfect introduction to benefit–cost analysis. The book closely integrates the theory and practice of benefit–cost analysis using a spreadsheet framework. The spreadsheet model is constructed in a truly original way which contributes to transparency, provides a check on the accuracy of the analysis, and facilitates sensitivity, risk and alternative scenario assessment. A case study incorporating the various issues is progressively developed on a spreadsheet with the links between each stage thoroughly explained. The complete case study spreadsheet can serve as a template for the reader's own appraisal of projects in the field. In addition to the worked examples in the text some exercises are appended at the end of each chapter. For further information please visit http://www.uq.edu.au/economics/bca